Komunikasi Krisis Pejabat Publik dan Resepsi Netizen (Viralitas Lagu Bupati Purwakarta 2026) - Sri Riski Wulandari; Muhammad Zia Ulhaq; Rahmat Kurniawan (CV. ITTC INDONESIA, 2026)
Public officials' social media crisis communication often fails to defuse public anger, particularly in crises touching on gender equality, as seen in the viral Sundanese song